2010
DOI: 10.1371/journal.ppat.1000789
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation, Distribution and γδ T Cell-Driven Regulation of IL-22-Producing T Cells in Tuberculosis

Abstract: Differentiation, distribution and immune regulation of human IL-22-producing T cells in infections remain unknown. Here, we demonstrated in a nonhuman primate model that M. tuberculosis infection resulted in apparent increases in numbers of T cells capable of producing IL-22 de novo without in vitro Ag stimulation, and drove distribution of these cells more dramatically in lungs than in blood and lymphoid tissues. Consistently, IL-22-producing T cells were visualized in situ in lung tuberculosis (TB) granuloma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
127
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 70 publications
(135 citation statements)
references
References 38 publications
8
127
0
Order By: Relevance
“…Blood samples collected freshly from all groups of participants were handled, and analyzed by phenotyping and intracellular cytokine staining (ICS) at the biocontainment laboratory [12]. Peripheral blood mononuclear cells (PBMCs) were isolated from heparin-anticoagulated blood by density gradient sedimentation using Lympholyte-H (Cedarlane Laboratories Ltd, Ontario, Canada).…”
Section: Immunofluorescence Staining and Flow Cytometric Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Blood samples collected freshly from all groups of participants were handled, and analyzed by phenotyping and intracellular cytokine staining (ICS) at the biocontainment laboratory [12]. Peripheral blood mononuclear cells (PBMCs) were isolated from heparin-anticoagulated blood by density gradient sedimentation using Lympholyte-H (Cedarlane Laboratories Ltd, Ontario, Canada).…”
Section: Immunofluorescence Staining and Flow Cytometric Analysismentioning
confidence: 99%
“…HMBPP belongs to phosphoantigen and only TCRs bearing both the Vγ2 and Vδ2 elements can recognize HMBPP. The phosphoantigen compound HMBPP used in the study was 98% pure and specifically stimulated the activation/expansion of Vγ2Vδ2 T cells but not other cell subpopulations [12].…”
Section: Intracellular Cytokine Stainingmentioning
confidence: 99%
See 2 more Smart Citations
“…For bacterial infection, it is generally accepted that IL-22 plays a protective role in extracellular bacterial infections, such as Citrobactor rodentium (6), Klebsiella pneumoniae (7) and segmented filamentous bacterium (SFB) (12), but its role in intracellular bacterial infections remains largely unclear. In the limited studies on intracellular bacterial infections, IL-22 was found redundant for Francisella tularensis (13) and Listeria monocytogenes (14) infections, although its role in Mycobacterium tuberculosis infection appeared inconsistent (15,16).…”
Section: Introductionmentioning
confidence: 99%